2018
DOI: 10.1109/twc.2017.2764891
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic Relaying and Random Linear Network Coding for Secure and Reliable Communication

Abstract: Opportunistic relaying has the potential to achieve full diversity gain, while random linear network coding (RLNC) can reduce latency and energy consumption. In recent years, there has been a growing interest in the integration of both schemes into wireless networks in order to reap their benefits while taking into account security concerns. This paper considers a multi-relay network, where relay nodes employ RLNC to encode confidential data and transmit coded packets to a destination in the presence of an eav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…For satisfying the interference constraint at primary networks, the quality of the link between secondary source and the secondary destination is poor due to the limited transmission power of secondary networks . The cooperative communication technology can reduce the path loss and improve the system capacity by using the relay nodes between the source node and the destination node under the condition of without increasing the transmission power, so the underlay cognitive radio network, which uses cooperative communication technology, ie, underlay cognitive cooperative networks, is a promising approach to boost the performance of secondary system transmission, without increasing the transmit power of secondary users while satisfying the interference power constraint at primary users. When relay nodes take part in cooperative communication in a full‐duplex mode in cognitive cooperative networks, it can further enhance the spectrum efficiency and the system capacity in the cognitive cooperative networks .…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For satisfying the interference constraint at primary networks, the quality of the link between secondary source and the secondary destination is poor due to the limited transmission power of secondary networks . The cooperative communication technology can reduce the path loss and improve the system capacity by using the relay nodes between the source node and the destination node under the condition of without increasing the transmission power, so the underlay cognitive radio network, which uses cooperative communication technology, ie, underlay cognitive cooperative networks, is a promising approach to boost the performance of secondary system transmission, without increasing the transmit power of secondary users while satisfying the interference power constraint at primary users. When relay nodes take part in cooperative communication in a full‐duplex mode in cognitive cooperative networks, it can further enhance the spectrum efficiency and the system capacity in the cognitive cooperative networks .…”
Section: Overviewmentioning
confidence: 99%
“…And d−i = P i P p +1 according to (8), the molecules and the denominator of (18) are divided by 2, respectively, we have…”
Section: System Modelmentioning
confidence: 99%
“…In particular, securing information with the injection of artificial noise to confuse the eavesdropper is one of the fundamental techniques in PLS which has been widely studied in the literature [13], [14]. There are several works studying the benefits of network coding in a PLS framework [15], [16], [17]. For example, Khan et al in [15] studied the intrinsic nature of RLNC against eavesdropping attacks and identified the advantage of optimising the number of source transmissions based on feedback by the legitimate destination.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, RLC can achieve the multicast capacity [18], [20]. Moreover, the inherent properties of RLC make it a suitable candidate for cases where the objective is not only to improve network reliability but also energy consumption [21], routing complexity [22], storage efficiency [23] and security [24].…”
Section: Introductionmentioning
confidence: 99%